The Effect of Dental and Oral Health Education with Animated Video Media and Props (Phantom) Teeth Brushing Behaviorin Asy-Syati'iyah Madrasah and Baitul Quran Kendari in 2021 - Welliam, Desih; Tasnim, Tasnim; Asri, Andi (Waluya The International Science of Health Journal, 2022)
Introduction: Dental and oral health is an essential element of a person's physical and mental health and well-being. Dental and oral health can describe physiological, psychological and social conditions, and play an important role in the quality of life. Dental and oral health education activities can increase a person's awareness to use dental and oral health services so as to reduce the severity of dental and oral diseases. Method: This research is a quantitative research type with a pre-experimental design. This research will be conducted in Madrasah Tsanawiyah Asy-Syati;iyah and Baitul Quran Kendari. The population in this study were students of Madrasah Tsanawiah Asy-Syati'iyah and Baitul Quran, totaling 128 students Result: The results of this study indicate the effect of dental and oral health education with animated video media on tooth brushing behavior in Madrasah Tsanawiyah Asy-Syati'iyah. There is an effect of dental and oral health education with props (phantom) on the behavior of brushing teeth in Baitul Quran Kendari. It was concluded that there were differences in the effect of dental and oral health education with animated video media and visual aids (phantom) on tooth brushing behavior in Madrasah Tsanawiyah Asy-Syati'iyah and Baitul Quran Kendari with p value 0.0012 (p <0.05). Conclusion: Suggestions in this study are expected to the education office to increase students' knowledge in maintaining dental and oral health.